Handbook of Cliometrics - Diebolt, Claude; Haupert, Michael; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg(Imprint), 2016)
The Handbook of Cliometrics is a milestone in the field of historical economics and econometric history through its emphasis on the concrete contribution of cliometrics to our knowledge in economics and history. The articles in the handbook authored by the leading scholars in the fields, stress the usefulness of cliometrics for economists, historians and social scientists in general. The Handbook offers a comprehensive coverage of topics with each article providing an overview of the contributions of cliometrics to a particular topic. The Handbook sets a new standard of quality in the field by offering a world-wide forum of discussion in cliometrics.
Family reconstitution data: a cliometric view -- History of cliometrics -- Growth theories -- Cliometric approaches to war -- GDP and convergence in modern times -- Cliometrics and the great depression -- Financial Systems -- Cliometric approaches to international trade -- Time series -- The industrial revolution: a cliometric perspective -- The cliometric study of financial panics and crashes.
Keywords: Econometrics; Mathematics; Economic Theory/Quantitative Economics/Mathematical Methods; History, general; Game Theory, Economics, Social and Behav. Sciences